Stability Constants of the Complexes of N-Salicylidene-p-x-Aniline (Where x = H, CH3, OCH3, NO2) with Co(II) - Abdullah, Bayazeed H. (Sulaimani Journal for Pure and Applied Sciences, 2001)
Stability constants of the complexes formed by Co(1l) whith N-Salicylidene-p-x-aniline (Where x = H, CH, , OCH3, NO2) have been determined by two spectrophotometric methods, in 50% ( v / v) ethanol at 22 + 0.5° , pH = 9 , and 0.019 Al (KNO3) ionic strength. The values of the stability constants have also been discussed.